THE ENVIRONMENTAL COST OF DYSTOPIA: AN ECOCRITICAL STUDY OF LEILA - Panmei, Pousuaikingliu Rikhi; Lourembam, Dhanamanjuri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Prayaag Akbar’s Leila constructs a dystopian imaginary where ecological degradation and authoritarian violence are deeply entwined. While critical discourse has primarily examined the novel through the lenses of caste, gender, and religious exclusion, this paper argues that the recurring motifs of toxic air, water scarcity, and sterilized landscapes reveal a material ecology of control through which authoritarian power is enacted. Shalini’s longing for her daughter, coupled with her memories of a freer and greener past, emerges as an affective counter-discourse to the spatial and ecological violence of segregation walls and urban decay. Drawing on ecocritical theory, the analysis demonstrates how Leila dramatizes the inseparability of environmental collapse and social injustice, positioning ecological loss as both symptom and instrument of political domination. In doing so, the novel reveals the entanglement of environmental and socio-political crises, highlighting the necessity of ecocritical engagements with contemporary dystopian fiction in the context of climate emergency and authoritarianism.